New case of true mimicry in cockroaches (Blattodea). Issue 1 (11th June 2012) - Schmied, Heiko; Lambertz, Markus; Geissler, Peter
Abstract True mimicry is an extremely rare phenomenon in cockroaches, with beetles as their favorite models. So far, only very few Pseudophyllodromiinae could be identified that conform to all requirements for Batesian mimicry and similarly exist only isolated reports on Müllerian mimicry. The vast majority, however, of the so‐called beetle‐mimicking cockroaches only shows a high degree of generalized convergence regarding their outer appearance. Specific models or counterparts, respectively, are lacking. Here we report on a last instar nymph of an undescribed Blattinae (Blattodea: Blattidae) that accurately mimics a truly harmful, sympatric carabid beetle. Although no indications for inedibility of this cockroach became evident, thus making Batesian mimicry likely, Müllerian mimicry can not be excluded with certainty. At any rate, this represents both the first case of mimicry in Blattidae and the first case with a ground beetle (Carabidae) as model for a cockroach mimic.